Novel Cre-Expressing Mouse Strains Permitting to Selectively Track and Edit Type 1 Conventional Dendritic Cells Facilitate Disentangling Their Complexity in vivo - Mattiuz, Raphaël; Wohn, Christian; Ghilas, Sonia; Ambrosini, Marc; Alexandre, Yannick O.; Sanchez, Cindy; Fries, Anissa; Vu Manh, Thien-Phong; Malissen, Bernard; Dalod, Marc; Crozat, Karine (Frontiers in Immunology, 2018)
Type 1 conventional DCs (cDC1) excel in the cross-priming of CD8+ T cells, which is crucial for orchestrating efficient immune responses against viruses or tumors. However, our understanding of their physiological functions and molecular regulation has been limited by the lack of proper mutant mouse models allowing their conditional genetic targeting. Because the Xcr1 and A530099j19rik (Karma/Gpr141b) genes belong to the core transcriptomic fingerprint of mouse cDC1, we used them to engineer two novel Cre-driver lines, the Xcr1Cre and KarmaCre mice, by knocking in an IRES-Cre expression cassette into their 3’-UTR. We used genetic tracing to characterize the specificity and efficiency of these new models in several lymphoid and non-lymphoid tissues, and compared them to the Clec9aCre mouse model, which targets the immediate precursors of cDCs. Amongst the three Cre-driver mouse models examined, the Xcr1Cre model was the most efficient and specific for the fate mapping of all cDC1, regardless of the tissues examined. The KarmaCre model was rather specific for cDC1 when compared with the Clec9aCre mouse, but less efficient than the Xcr1Cre model. Unexpectedly, the Xcr1Cre model targeted a small fraction of CD4+ T cells, and the KarmaCre model a significant proportion of mast cells in the skin. Importantly, the targeting specificity of these two mouse models was not changed upon inflammation. A high frequency of germline recombination was observed solely in the Xcr1Cre mouse model when both the Cre and the floxed alleles were brought by the same gamete irrespective of its gender. Xcr1, Karma and Clec9a being differentially expressed within the cDC1 population, the three CRE-driver lines examined showed distinct recombination patterns in cDC1 phenotypic subsets. This advances our understanding of cDC1 subset heterogeneity and the differentiation trajectory of these cells. Therefore, to the best of our knowledge, upon informed use, the Xcr1Cre and KarmaCre mouse models represent the best tools currently reported to specifically and faithfully target cDC1 in vivo, both at steady state and upon inflammation. Future use of these mutant mouse models will undoubtedly boost our understanding of the biology of cDC1.